1929
DOI: 10.1084/jem.50.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-Immunological Studies on Conjugated Carbohydrate-Proteins

Abstract: 1. When two chemically different carbohydrate derivatives are bound to the same protein, the newly formed antigens exhibit distinct immunological specificity. 2. When the same carbohydrate radical is conjugated with two chemically different and serologically distinct proteins both of the sugar-proteins thus formed acquire a common serological specificity. 3. The newly acquired specificity of the artificially prepared sugar-proteins is determined by the chemical constitution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1

Year Published

1935
1935
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(78 citation statements)
references
References 1 publication
(1 reference statement)
1
71
1
Order By: Relevance
“…Because of the extreme age dependence of the human antipolysaccharide response, however, CP vaccine is ineffective in infants (16)(17)(18). Another seminal finding of the Rockefeller group, shown with pneumococcus, was that coupling of CPs or even their immunodeterminant sugars to carrier proteins increases the CP-reactive antibody response (19,20). Five decades later, this approach was used for conjugate CP vaccines to protect infants against the capsulated pathogen Haemophilus influenzae type b (21)(22)(23).…”
Section: History Of Vaccinationmentioning
confidence: 99%
“…Because of the extreme age dependence of the human antipolysaccharide response, however, CP vaccine is ineffective in infants (16)(17)(18). Another seminal finding of the Rockefeller group, shown with pneumococcus, was that coupling of CPs or even their immunodeterminant sugars to carrier proteins increases the CP-reactive antibody response (19,20). Five decades later, this approach was used for conjugate CP vaccines to protect infants against the capsulated pathogen Haemophilus influenzae type b (21)(22)(23).…”
Section: History Of Vaccinationmentioning
confidence: 99%
“…The first generation of vaccines ended following the development of purified polysaccharide vaccine to combat meningococcus serogroups A, C, Y, and W (Austrian et al 1976), as well as Haemophilus influenza type b (Anderson et al 1972). The development in the use of purifiedpolysaccharide based vaccines then lead to the development of conjugate vaccines, in which the polysaccharides were conjugated to a protein (Avery andGoebel 1929, Robbins andSchneerson 1990).…”
Section: History Of Vaccinationmentioning
confidence: 99%
“…They observed that weak immunogenicity of polysaccharide antigen of streptococcus pneumonia type 3 increased by its connection to the carrier protein in rabbit. These observations led to a foundation for producing modern conjugate vaccines (42). In 1987, hemophilus influenza B (HIB) was the first conjugate vaccine, which could obtain license for medical usage and was later used for immunization of infants.…”
Section: Conjugated Vaccinesmentioning
confidence: 99%